The Other Species Capability & the Power of Wonder. Issue 1 (2nd January 2021) - Bendik-Keymer, Jeremy
ABSTRACT: I argue that the Other Species Capability (OSC) in Martha Nussbaum's Capability Approach deserves a more central place in our thinking about human capability than has often been thought. In order to do so, I explain how the OSC protects the human power of biocentric wonder, which in turn has a power that is architectonic in some ways even to capabilities such as Practical Reason and Affiliation. The bulk of the paper explains the main history surrounding the OSC, what biocentric wonder is, why it should relate to an expanded understanding of freedom, and how these things relate to self-reflection and our capacity for moral regard. Our capacity to relate to other species ought to be seen as central to our ability to come to terms with who we are and to grasp moral regard for each other.